2021
DOI: 10.1186/s12969-020-00488-9
|View full text |Cite
|
Sign up to set email alerts
|

Early combination therapy with etanercept and methotrexate in JIA patients shortens the time to reach an inactive disease state and remission: results of a double-blind placebo-controlled trial

Abstract: Background Remission is the primary objective of treating juvenile idiopathic arthritis (JIA). It is still debatable whether early intensive treatment is superior in terms of earlier achievement of remission. The aim of this study was to evaluate the effectiveness of early etanercept+methotrexate (ETA+MTX) combination therapy versus step-up MTX monotherapy with ETA added in refractory disease. Methods A multi-centre, double-blind, randomized study … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…The number of patients was small, and we were unable to make a comparison between patients who received synthetic DMARDs compared with TNFi. In addition, because none of the participants received a combined biologic and synthetic DMARD treatment, we were unable to show the potential benefits of additional treatment (if any) as seen in other studies 12,16 …”
Section: Discussionmentioning
confidence: 94%
“…The number of patients was small, and we were unable to make a comparison between patients who received synthetic DMARDs compared with TNFi. In addition, because none of the participants received a combined biologic and synthetic DMARD treatment, we were unable to show the potential benefits of additional treatment (if any) as seen in other studies 12,16 …”
Section: Discussionmentioning
confidence: 94%
“…A total of 9 studies compared bDMARD or JAK inhibitor arms with placebo, and 3 studies compared with methotrexate monotherapy. In the Alexeeva ( 20 ) study, etanercept combined with methotrexate was compared against methotrexate monotherapy; in the ACUTE-JIA study, infliximab combined with methotrexate was compared against methotrexate monotherapy; and in the BeSt for Kids study, the control arm was methotrexate or sulfasalazine. In the RAPPORT study, the control arm was placebo for the first 4 weeks and then switched to rilonacept until the end of the study.…”
Section: Resultsmentioning
confidence: 99%
“…Etanercept is a fusion protein consisting of a Fc portion of immunoglobulin G linked to human TNF-α receptor with potent antiinflammatory activities, competitively inhibiting the binding of TNF-α to cell surface receptors and attenuating its biological effects. A number of studies have revealed the good effect and safety of etanercept for the treatment of rheumatoid arthritis, JIA, psoriatic arthritis, ankylosing spondylitis and psoriasis (10,(24)(25)(26)(27). Etanercept biosimilar recombinant human TNF-α receptor II: IgG Fc fusion protein (rhTNFR-Fc) is a TNF-α inhibitor targeting soluble TNF-α to inhibit its interaction with cellsurface receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to those treated with the standard step-up regimen, more patients treated with a combination of etanercept plus MTX reached better response and achieved inactive disease and remission more rapidly ( 26 ). The majority of children with JIA can attain inactive disease within 2 years, even many being able to discontinue treatment ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation